Inequality-based approximation of matrix eigenvectors - Kocsor, András; Dombi, József; Bálint, Imre (Zielona Góra: Uniwersytet Zielonogórski)
A novel procedure is given here for constructing non-negative functions with zero-valued global minima coinciding with eigenvectors of a general real matrix A. Some of these functions are distinct because all their local minima are also global, offering a new way of determining eigenpairs by local optimization.
Keywords: eigenvectors; eigenvalues; inequalities; error bounds; iterative methods